Socio-legal approaches to international economic law. - Perry-Kessaris, Amanda (Taylor and Francis, 2013)
This collection explores the analytical, empirical and normative components that distinguish socio-legal approaches to international economic law both from each other, and from other approaches. It pays particular attention to the substantive focus (what) of socio-legal approaches, noting that they go beyond the text to consider context and, often, subtext. In the process of identifying the 'what' and the 'how' (analytical and empirical tools) of their own socio-legal approaches, contributors to this collection reveal why they or anyone else ought to bother--the many reasons 'why' it is imp.